Pengaruh Kompensasi Dan Kepemimpinan Terhadap Kinerja Karyawan Pada Rumah Sakit Umum Materna Medan - Elisa Wijaya; Amrin Fauzi; Fajrillah Fajrillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Rumah Sakit Umum Materna Medan is a health care site that implement health care institutions as well as health education and research. Human resources is a very important role in a company, and therefore companies need to pay attention to the welfare of its employees. One way to compensate. Besides, compensation is also useful to provide motivation to employee for increasimg the performance that gives good results for the company. As for the purpose of this research is to analyze the effect of compensation and leadership to employees performance at Rumah Sakit Umum Materna Medan by indentifying how the data by gender, education, and age as well as the compensation and leadership system imposed company. In completing this thesis, methods of data analysis used is multiple linear regression method to test more than one independent variable. The results of simultameous testing positive impact although the effect is small. While partial compensation and leadership influence on the performance of employees at Rumah Sakit Umum Materna Medan. Rumah Sakit Umum Materna Medan terrain need to improve the system of compensation and leadership to employees to improve performance